The Contested Terrain of Critical Pedagogy and Teaching Informal Education in Higher Education - Alan Smith; Mike Seal (MDPI AG, 2021)
This review explores how critical pedagogy, often cited by educators of informal educators as a key influence, actually informs teaching of informal educators in higher education and assesses its potential to do so. It explores the background to critical pedagogy, its principles, aims and approaches and examines its worldwide influence on the teaching of informal educators. The authors argue that critical pedagogy is crucial for the teaching of informal educators, enabling lecturer and practitioners to interrupt the hegemony of neo-liberal and neo-managerial thinking in their practice and in higher education, and re-orientate themselves and examine their positionality within their institutions. It will focus on practical examples of enabling critical pedagogy in the teaching of informal education in higher education institutions.